2020
DOI: 10.1038/s41419-020-03144-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting BCL-2 in B-cell malignancies and overcoming therapeutic resistance

Abstract: Defects in apoptosis can promote tumorigenesis and impair responses of malignant B cells to chemotherapeutics. Members of the B-cell leukemia/lymphoma-2 (BCL-2) family of proteins are key regulators of the intrinsic, mitochondrial apoptotic pathway. Overexpression of antiapoptotic BCL-2 family proteins is associated with treatment resistance and poor prognosis. Thus, inhibition of BCL-2 family proteins is a rational therapeutic option for malignancies that are dependent on antiapoptotic BCL-2 family proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
118
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(120 citation statements)
references
References 121 publications
(160 reference statements)
2
118
0
Order By: Relevance
“…B-cell lymphoma-2 (BCL-2) proteins regulate the intrinsic mitochondrial apoptotic pathway and represent another therapeutic target in B-cell malignancies (66). Venetoclax is an approved, highly selective BCL-2 inhibitor used in treatment of patients with CLL.…”
Section: Future Studiesmentioning
confidence: 99%
“…B-cell lymphoma-2 (BCL-2) proteins regulate the intrinsic mitochondrial apoptotic pathway and represent another therapeutic target in B-cell malignancies (66). Venetoclax is an approved, highly selective BCL-2 inhibitor used in treatment of patients with CLL.…”
Section: Future Studiesmentioning
confidence: 99%
“…Under the influence of BTK inhibition by targeted drugs, CLL cells and malignant B-cells in other lymphoid neoplasms may adapt and compensate for the blocked BTK axis by activating the PI3K/Akt/Erk pathway [ 21 , 22 , 41 ]. Functional analyses by Spina et al in cells from ibrutinib-treated patients revealed that the BCR pathway through Akt and Erk was still inducible upon stimulation of the B-cell receptor in spite of effective inhibition of the BTK/PLCy2 pathway [ 22 ].…”
Section: Mechanisms Of Resistance To Btk Inhibitionmentioning
confidence: 99%
“…Two key members of MAPK family, JNK (c-Jun N-terminal kinase) and ERK (extracellular signal-regulated kinase), can dissociate Bcl-2/Beclin-1 or Bcl-xL/Beclin-1 complexes to release Beclin-1, resulting in autophagy. Bcl-2 and Bcl-xL belong to anti-apoptotic Bcl-2 protein family, levels of which will be decreased during apoptosis [14].…”
Section: Introductionmentioning
confidence: 99%